Insights into the Regulatory Role of Non-coding RNAs in Cancer Metabolism - Beltrán-Anaya, Fredy O.; Cedro-Tanda, Alberto; Hidalgo-Miranda, Alfredo; Romero-Cordoba, Sandra L. (Frontiers in Physiology, 2016)
Cancer represents a complex disease originated from alterations in several genes leading to the disturbances of important signaling pathways in tumor biology favoring heterogeneity that promotes adaptability and pharmacological resistance of tumor cells. Metabolic reprogramming has emerged as an important hallmark of cancer characterized by the presence of aerobic glycolysis, increased glutaminolysis and fatty acid biosynthesis, as well as an altered mitochondrial energy production. The metabolic switches that support energetic requirements of cancer cells are closely related to either activation of oncogenes or down-modulation of tumor-suppressor genes, finally leading to dysregulation of cell proliferation, metastasis and drug resistance signals. Non coding RNAs (ncRNAs) have emerged as one important kind of regulatory molecules of the altered genes contributing to the establishment of metabolic reprogramming. Moreover, diverse metabolic signals can regulate ncRNAs expression and activity at genetic, transcriptional or epigenetic level. The regulatory landscape of ncRNAs may provide a new approach for understanding and treatment of different kind of malignancies. In this review we discuss the regulatory role exerted by ncRNAs on metabolic enzymes and pathways involved in glucose, lipid and amino acid metabolism. We also review how the metabolic stress conditions and tumoral microenvironment influence ncRNA expression and activity. Furthermore, we comment the therapeutic potential of metabolism-related ncRNAs in cancer.